2023
DOI: 10.1021/acscatal.3c02950
|View full text |Cite
|
Sign up to set email alerts
|

Extending the π-Conjugated System in Conjugated Microporous Polymers to Modulate Excitonic Effects for Metal-Free Selective CO2 Photoreduction to CH4

Fanyu Meng,
Juan Wang,
Minghui Chen
et al.

Abstract: Photocatalytic CO 2 reduction into CH 4 is an appealing approach to alleviate the current energy and environmental crisis; however, achieving high selectivity and conversion efficiency still remains challenging. The rational design of photocatalysts for CO 2 adsorption and activation is thus crucial. Here, we designed and synthesized two redox-active truxene-based conjugated microporous polymers linked by thiazolo [5,4-d]thiazole for metalfree photocatalytic reduction of CO 2 to CH 4 . Significantly, the optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(11 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…TpBpy–Ir and TpBpy–Ru exhibited higher transient photocurrents and lower resistances compared to those of TpBpy, indicating their stronger ability for separating and transferring charges (Figure S15). , …”
Section: Resultsmentioning
confidence: 99%
“…TpBpy–Ir and TpBpy–Ru exhibited higher transient photocurrents and lower resistances compared to those of TpBpy, indicating their stronger ability for separating and transferring charges (Figure S15). , …”
Section: Resultsmentioning
confidence: 99%
“…According to these findings, as π‐conjugation increased, so did absorption and emission, resulting in a red shift. A review of the literature on organic chromophoric systems revealed that the more conjugated the π‐system, the longer the wavelength of photon captured [28,29] . The proven fact is that compounds having a sufficient number of conjugated bonds in their molecular core may absorb light photons in the visible area, resulting in compounds of yellow to red color.…”
Section: Resultsmentioning
confidence: 99%
“…A review of the literature on organic chromophoric systems revealed that the more conjugated the π-system, the longer the wavelength of photon captured. [28,29] The proven fact is that compounds having a sufficient number of conjugated bonds in their molecular core may absorb light photons in the visible area, resulting in compounds of yellow to red color. Figure 1c shows that αcyanostilbene CYS is a white compound in visible light and emits blue light when exposed to UV light irradiation (λ ex .…”
Section: Photophysical Properties Evaluations Of Conjugates Cys and Bcysmentioning
confidence: 99%
“…In the past few decades, covalent organic frameworks (COFs) 1–3 have received great attention for applications including but not limited to gas separation and storage, 4,5 catalysis 6,7 and sensing 8–11 due to their highly tunable structures and compositions. 12–15 The electronic structures of resultant COFs can readily be tuned by tailoring the organic building units, among which the photofunctional COFs exhibit a wide range of potential applications, such as photocatalytic carbon dioxide reduction, 16–19 hydrogen peroxide production 20–22 and hydrogen generation. 23,24…”
Section: Introductionmentioning
confidence: 99%